1963
DOI: 10.1126/science.141.3586.1188
|View full text |Cite
|
Sign up to set email alerts
|

Tremorine: Its Effect on Amines of the Central Nervous System

Abstract: The administration of tremogenidine doses of Tremorine, 1,4-dipyrrolidino-2 butyne, is followed by a significant decrease in the concentration of norepinephrine in the brain stem of three common laboratory species. The change in the concentration proceeds at a rate which coincides with the occurrence of the tremor in each of these species. In the rat, the change in norepinephrine is followed by a progressive increase in the concentration of 5-hydroxytryptamine in the brain stem. Bilateral adrenalectomy in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
1

Year Published

1967
1967
1980
1980

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 6 publications
0
6
1
Order By: Relevance
“…Vas (1966), however, did not observe any effect of propranolol in Parkinsonian tremor.Friedman (1963) andFriedman, Aylesworth &Friedman (1963) have shown that tremorine lowers the noradrenaline levels in the brains of rats, mice and guinea-pigs but fails to do so in rabbits, which do not show tremor after the administration of tremorine.These findings indicate that brain catecholamines may have a role in causing tremor and the present work was undertaken to study their role in, and the effect of, a recent adrenergic f,-receptor blocking drug-namely, dextro-N-isopropyl-para-nitrophenylethanolamine (d-INPEA)-on tremorine and harmaline induced tremor in mice. …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Vas (1966), however, did not observe any effect of propranolol in Parkinsonian tremor.Friedman (1963) andFriedman, Aylesworth &Friedman (1963) have shown that tremorine lowers the noradrenaline levels in the brains of rats, mice and guinea-pigs but fails to do so in rabbits, which do not show tremor after the administration of tremorine.These findings indicate that brain catecholamines may have a role in causing tremor and the present work was undertaken to study their role in, and the effect of, a recent adrenergic f,-receptor blocking drug-namely, dextro-N-isopropyl-para-nitrophenylethanolamine (d-INPEA)-on tremorine and harmaline induced tremor in mice. …”
mentioning
confidence: 99%
“…Friedman (1963) andFriedman, Aylesworth &Friedman (1963) have shown that tremorine lowers the noradrenaline levels in the brains of rats, mice and guinea-pigs but fails to do so in rabbits, which do not show tremor after the administration of tremorine.…”
mentioning
confidence: 99%
“…At 160 C there was a clear increase, while at 6°C there was suggestive evidence of an increase. These findings may present an explanation for the conflicting reports quoted in the introduction (Friedman et al, 1963;Whittaker & Walaszek, 1964).…”
Section: Brain Aminesmentioning
confidence: 82%
“…Everett et al (8) suggested that the probable site of produc tion of tremorine tremor is at subcortical level. Evidences so far available show that there is disturbed me tebolism of catecholamines in the brain of patients with Parkinson's disease (9) and in rats brain after ad ministration of tremorigenic dcse of tremorine (10). The abolition of tremor by propranolol seems to sup port that catecholamines has some role in the causation of tremorigenic tremor and that of Parkinson's disease.…”
mentioning
confidence: 99%